2007
DOI: 10.1038/bdj.2007.32
|View full text |Cite
|
Sign up to set email alerts
|

Oral health of remand prisoners in HMP Brixton, London

Abstract: Remand prisoners have compromised general and oral health compared with the general population. They exhibit poor oral health, which is contributed to by their lifestyles and health behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
3
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 16 publications
12
59
3
5
Order By: Relevance
“…Volgens Matevosyan (2009) is vooral bij psychiatrische patiënten het belang van een goede mondgezondheid onderbelicht en behoeft mondzorg bij deze patiëntengroep meer aandacht. Onderzoeksresultaten over de mondgezondheid van personen in gevangenissen laten naar verhouding meer mondziekten zien (Heidari et al, 2007;McGrath, 2002;Werkhoven et al, 2004;BuunkWerkhoven et al, 2010a;Buunk-Werkhoven et al, 2010b). Door allerlei omstandigheden is preventieve mondzorg niet zonder meer vanzelfsprekend in de behandeling van justitiabelen.…”
Section: Inleidingunclassified
“…Volgens Matevosyan (2009) is vooral bij psychiatrische patiënten het belang van een goede mondgezondheid onderbelicht en behoeft mondzorg bij deze patiëntengroep meer aandacht. Onderzoeksresultaten over de mondgezondheid van personen in gevangenissen laten naar verhouding meer mondziekten zien (Heidari et al, 2007;McGrath, 2002;Werkhoven et al, 2004;BuunkWerkhoven et al, 2010a;Buunk-Werkhoven et al, 2010b). Door allerlei omstandigheden is preventieve mondzorg niet zonder meer vanzelfsprekend in de behandeling van justitiabelen.…”
Section: Inleidingunclassified
“…Arti cles detailing prevalence in a single prison population were more common than those that compared the prevalence in 'comparative' non-institutionalised populations resulting from National Surveys. 3,4,11,[16][17][18][19] One study compared the oral health of present or former her oin addict inmates to non-drug addict inmates, 15 another evaluated the health of female former substance abusers. 20 Due to the heterogeneous nature of the studies in terms of study design, institution type (state vs federal, single sex vs mixed), setting and population, data have not been synthesised.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Where clinical meas urements were taken, attempts were cedures, eg with reference to published standards of use 16 or guidelines, 1,2,7,21,22 though the number of teeth examined (28 vs 32) and/or the use of radiographs in the examination was not always specified. The attempt to reduce poten tial bias by standardising procedures was particularly evident for the com parator studies, 3,4,16 where assessment of the inmate population was closely related to the use of national or state studies. Despite standardisation and calibration measures being employed, only two studies explicitly reported reliability values.…”
Section: Potential Biasmentioning
confidence: 99%
See 2 more Smart Citations